The Effects of Eight-Week Regular Training in Amateur Amputee Football Team Athletes' Body Composition - Betül Akyol; Mehmet Ilkım; Burak Canpolat (Selcuk University, 2018)
The purpose of this study is to observe the effects of the 8 week regular training program on body composition of the amateur amputee sports club athletes. 12 amateur amputee athletes in the Malatya Ay Yildiz Amateur Amputee Football Team with ages ranging from 16 to 33 (X age: 24.33 ± 5.71 years, X length: 1.74 ± 8.07 meters, X weight: 75.09 ± 15.16 kg) voluntarily participated in this study. The training program consists of strength, strength, agility, speed, technique, tactics, coordination and flexibility.  Body length, body weight, heart rate measurements, skin fold thickness of three different parts and body mass index (BMI) were measured before and after the 8 week training period to evaluate body composition. Densities were calculated using the Jackson and Pollock (1978) formula, taking into account the skin fold thickness measurements made. Percent body fat is calculated using Siri's formula. The body mass index is determined by the World Health Organization (WHO) formula. A statistically significant difference was found in the comparison of the athletes' weight, resting heart rate, body mass index and body fat percentage in the first and last week measurements according to Wilcoxon signed rank test results (p lt;0.05).As a result, in this study; The 8-week training program which includes strength, strength, speed, agility, coordination, technique and flexibility enhancing exercises showed significant changes in parameters of body composition of Ay Yıldız Spor Kulubu ampute athletes.